Luigi Taborelli (2022), Stamped Medicine Flasks nei ‘Virginia R. Grace Papers’ e i pogressi della ricerca, Roma: Edizioni Quasar, [2022] - Totelin, Laurence (DELTOS, 2024)
Luigi Taborelli is the world expert on microcontainers produced in the Hellenistic period and stamped with the word ‘lukion’, referring to a medicinal preparation. In the book reviewed, Taborelli examines the archives of the famous American archaeologist Virginia Grace on the matter of these microcontainers. Examining archival material allows scholars to identify exemplars of these microcontainers which remain unexamined. As more examples of these microcontainers come to light, scholars will be able to better understand the trade in medicinal substances in the Hellenistic world.